Association of Accommodative Amplitude and Lag with Attention Deficit/Hyperactivity Disorder. - Hinkley, Sarah; Veldkamp, Abigail Faith; O'Beirne Naszradi, Kristen (Optometry & Visual Performance, 2016)
Background: Attention Deficit/Hyperactivity Disorder (ADHD) is one of the most common disorders diagnosed in children. Researchers have found links between tracking deficits, convergence insufficiency, and a diagnosis of ADHD, but little research exists on the relationship between accommodation and ADHD. This study investigates whether there is a correlation between ADHD and accommodation dysfunction. Methods: Patients aged 7-18 in the Pediatrics and Binocular Vision Service at the Ferris State University Eye Center presenting for a comprehensive eye examination were invited to participate in the study using an anonymous ADHD symptom survey produced and accredited by the American Pediatric Association or a stated previous diagnosis of ADHD. The student clinician or faculty member recorded the patient's amplitude of accommodation and accommodative lag at the conclusion of the eye examination in order to correlate the diagnosis. Results: Using t-test and chi-square analyses, a statistically significant link between lower- than-average lag of accommodation and ADHD was demonstrated (p=0.04 and p<0.1%, respectively). A link between amplitude of accommodation and attention disorders was not significant. Conclusions: While lower-than-average accommodative lag was shown to correlate with ADHD (established or symptom-based diagnosis), further investigation is necessary to determine whether accommodative amplitude correlates with ADHD.